Negotiating cultures : Delhi's architecture and planning from 1912 to 1962 - Guerrieri, Pilar Maria (Oxford University Press, 2018)
Negotiating Cultures' focuses on the city of Delhi, one of the largest mega-cities in the world, and examines from a historical perspective, the process of hybridization between cultures within its local architecture and urban planning from 1912 to 1962.